Financial Literacy and Cognitive Biases: Key Determinants of Gen Z Investment Choices - Ningtyas, Mega; Prajawati, Maretha Ika; munir, Misbahul (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study investigates the influence of financial literacy and cognitive biases on investment decisions among Gen Z investors in Indonesia. A cross-sectional descriptive survey design was employed, guided by a positivist epistemology. Data were collected from 229 respondents through an online questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the hypotheses. The results reveal that financial literacy and cognitive biases significantly impact investment decisions. Higher financial literacy is associated with more rational and informed investment choices. Conversely, cognitive biases, including hindsight bias and the illusion of control, strongly influence decision-making processes. These findings highlight the importance of targeted financial education programs to enhance financial literacy and reduce the effects of cognitive biases, enabling Gen Z investors to make better financial decisions. This study provides valuable insights for policymakers and educators to support the financial well-being of the younger generation.